An Unusual Case Report of Erupted Odontoma. (4th February 2013) - Mehta, Dhaval; Raval, Nilesh; Udhani, Sneha; Parekh, Viral; Modi, Chintan
Abstract : Odontomas are the most common of the odontogenic tumors of the jaws, which are benign, slow growing, and nonaggressive. They are usually asymptomatic and found in routine dental radiographic examination. Odontomas are usually associated with tooth eruption disturbances. Eruption of odontoma in oral cavity is rare entity. Here we report a case of an unusual erupted compound odontoma.